Implementations and applications of Renyi entanglement in Monte Carlo simulations of spin models - Inglis, Stephen (2013)
Although entanglement is a well studied property in the context of quantum systems, the ability to measure it in Monte Carlo methods is relatively new. Through measures of the Renyi entanglement entropy and mutual information one is able to examine and characterize criticality, pinpoint phase transitions, and probe universality. We describe the most basic algorithms for calculating these quantities in straightforward Monte Carlo methods and state of the art techniques used in high performance computing. This description emphasizes the core principal of these measurements and allows one to both build an intuition for these quantities and how they are useful in numerical studies.